Analysis and evaluation of Lithuanian public interest companies audit market - Vaicekauskas, Darius (Buhalterinės apskaitos teorija ir praktika, 2014)
The article investigates audit companies‘ specialization among the public interest companies of Lithuania. Prior literature explores various advantages of industry auditors – auditors who specialize in particular industries while enhancing the main part of clients in the industry branch. Industry auditors reach higher level of audit quality, while making more effective planning decisions, assessing more effectively client‘s business risk, as well as the risk of material misstatement, complying at highest rate with auditing standards. 154 public interests companies of Lithuania were analysed in order to assess whether the is a trend of auditors‘ specialization in a market of public interest companies in Lithuania. Results of the research imply auditors tending to specialize themselves in mainly all branches of industries, reaching highest rate of clients in particular industry of pension funds, investment funds and credit institutions. The results also disclose some evidence of industry auditors keeping their audit prices at higher level than their competitors, as well as their reputation being quite stable reaching more adds than losses. Issues concerning industry expertise auditors‘ quality significantly affects auditors‘ reputation. The results of the research taken support conclusions of vast body of prior researches on auditors‘ specialization implying that particular industry auditors may achieve and enhance higher level of audit quality.